Envisioning My Best Future Self: Integrating Positive Psychology and Prospection in Student Affairs Practice - Henry Mason (Journal of Student Affairs in Africa)
Students’ psychological well-being constitutes a critical issue that necessitates support and dedicated intervention from student affairs professionals. Positive psychology, focusing on future-oriented prospective thinking, offers valuable insights and methods relevant to student affairs. This paper leverages the principles of Positive Psychology, particularly prospection, and reports a qualitative study that explored how 45 university students (26 females and 19 males; age range: 18-23) conceived of their best future selves. Phenomenological analysis revealed a dynamic interplay between students’ optimistic visions of personal and professional success, and the pressing need for practical strategies to realise these aspirations. By integrating and leveraging Positive Psychology, particularly prospection-focused methodologies, practitioners can support students in envisioning their futures more clearly and translating ambitious visions into tangible outcomes, thereby fostering individual and collective growth.